Trigonometria, números complexos e aplicações - Lima, Thiago do Carmo (2015)
This study was divided into three parts: the right triangle trigonometry, trigonometry in trigonometric cycle, complex numbers. In the right triangle the sine values were defined, cosine, tangent, cotangent, cosecant and drying of the remarkable angles: 18°, 30º, 45°, 60º beyond its derivations. Important properties as the fundamental trigonometric relationship were demonstrated. Trigonometric cycle in addition to the resulting properties of the right triangle were presented and other proven as the laws of sine and cosine, trigonometric relationship of angles greater then 90º and the sum and difference of arcs, trigonometric equations. In the complex numbers was made the number in their properties along with the algebraic and geometric forms a complex number. At this point it has been seen trigonometric to the importance of the development of Moivre formula. In the appendix we have tasted the powers of the number (i) and the trigonometric table.